No compromise on principles and policies - Abd. Aziz Ishak (Petaling Jaya, Selangor : Malayan Times, 1963)
This volume contains a collection of the speeches made by Enche Abdul Aziz during the year 1956 to 1960 inside and outside of Parliament. These selections will give the reader an insight into his activities, the projects completed, and his blueprints, which formed the sum total of his contributions to the development of the New Malaya.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Community development -- Malaysia; Rural development -- Malaysia